Body talk : how to embrace your body and start living your best life - Sturino, Katie (Clarkson Potter/Publishers, 2021)
"Learn to love yourself and body with this interactive guide from the body acceptance advocate, influencer, and founder of Megababe beauty. Can you imagine how much free time you'd have if you didn't spend so much of it body shaming yourself? Katie Sturino knows all too well what it's like to shit talk yourself. She spent thirty years of her life feeling ashamed of her body and its self-determined wrongness. Now she doesn't care what anyone thinks of her; she only cares that she's happy and comfortable with herself. Body positivity and size inclusivity is still a relatively new phenomenon, but Sturino has dedicated her life to unlearning all that beauty standard BS and uses her blog, Instagram, podcast, and non-toxic, solution-oriented beauty products to share the message that changed her life: YOUR BODY IS NOT THE PROBLEM. With Body Talk, an illustrated guide-meets-workbook, Sturino is here to help you stop obsessing about your body issues, focus on self-love, and free up space in your brain for creative and productive energy. Complete with empowering affirmations, relatable anecdotes, and actionable takeaways, as well as space to answer prompts and jot down feelings and inspirations, Body Talk encourages you to spend less time thinking about how you look and what you eat and more time discovering your inner fierceness."--Publisher's website.